CONTENT ANALYSIS OF ARABIC VOCABULARY IN AL QURAN FOR THE IMPROVEMENT OF EMOTIONAL INTELLIGENCE - Salsabila, Octa Syakila; Almimbar, Alvi Huda; Kadir, Muh Ahyar; Mustofa, Syaiful; Faslah, Redho (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2024)
Arabic language has a strong effect on improving human emotional intelligence. Emotional intelligence has been explained in the verses of the Quran, which state that learning Arabic will strengthen one’s understanding of science as well as strengthen the soul. This study aims to analyze Arabic vocabulary for emotional intelligence in the Quran. This research used a qualitative approach with a content analysis method. The research design was a literature study. The data analysis process involved selecting, collecting, analyzing, coding, and describing Quranic verses. The results of this study explained that in analyzing Arabic vocabulary for emotional intelligence from the verses of the Quran, the authors have collected twenty words, including la taiashu (do not despair), likaylâ ta'sau (so that you do not grieve), la tafrah (do not be joyful), dzu an-nun (degree), ghadab wa ashifa (anger and heatful), fastaqim (be steadfast), kadhuma (to suppress), tadabbara (to ponder), al-jahra bi as-su'i (publicly proclaiming evil), la tahinu (do not be weak), adz-dzauq (taste), isyrah (expansion or relief), la talmizu wa la tanabazu (do not backbite or slander), hanaan (compassion), ulil albab (people of understanding), mukhlisin (sincere), shobaruu (they have endured patiently), farihuu (they rejoiced), taqnathuu (they despair), and tathmai'nnu (they are content).